Investigation on Damage Mechanisms of PE Self-reinforced Composites by Acoustic Emission Technology (Journal of Fiber Bioengineering and Informatics, 2012)
The purpose of this study is to investigate the damage mechanisms in UHMWPE/LDPE laminatedby Acoustic Emission (AE) technique. Model specimens are fabricated to obtain expected damagemechanisms during tensile testing. Then, relationship among AE descriptors is studied by hierarchicalcluster analysis, and AE signals are classified by k-means algorithm. Finally, an Artificial Neural Network(ANN) is created and trained by various optimal algorithms to identify damage mechanisms. The resultsreveal that typical damage mechanisms in PE self-reinforced composite can be classified in terms of thesimilarity between AE signals and identified by a well trained ANN.